CULTURAL PRACTICES AND MATHEMATICAL THINKING ABILITY AMONG HAUSA AND YORUBA SECONDARY SCHOOL STUDENTS IN KANO AND OYO STATE, NIGERIA - Shuaibu, Dr.Garba (Journal of Technical Education and Training, 2014)
This study examines cultural practice, and mathematical thinking ability based on Activity Theory Dimension as a booster to Science and Technology Education with particular reference to Hausa and Yoruba secondary school students in Kano and Oyo states. A non-experimental causal-comparative design was employed for the study. The populations comprised all the secondary schools in Kano and Oyo states. 10 secondary schools were randomly selected five from each state out of the 517 senior secondary schools in Kano   and 805 senior secondary schools in Oyo states. In addition, a sample comprising 370 teachers and students were purposively selected from the target population of 246,746 teachers and 579,744 students.  Two instruments were used to collect data namely, the Teachers Evaluation of Mathematical Thinking Ability Questionnaire (TEMTAQ) and the Students Mathematical Thinking Ability Questionnaire (SMTAQ). Three Research questions and two research hypotheses were generated and formulated to guide the investigation. Data collected were analysed using descriptive and inferential statistics. The findings indicate that the level of mathematical thinking ability among both groups of students is good and their cultural practices can be seen to be an influencing factor in promoting this ability. While no difference in mathematical thinking ability between Hausa and Yoruba, statistically significant difference was obtained between urban and rural students irrespective of ethnicity. Rural students irrespective of ethnicity have been found to have greater mathematical thinking ability compared to urban students which may be attributed to differences in urban and rural culture. In conclusion, Yoruba and Hausa culture equally support mathematical thinking development of secondary school students in Kano and Oyo states, and living in rural area is associated with higher mathematical thinking ability of either groups.